2017
DOI: 10.1097/md.0000000000005321
|View full text |Cite|
|
Sign up to set email alerts
|

Assessment of hepatocellular carcinoma risk based on peg-interferon plus ribavirin treatment experience in this new era of highly effective oral antiviral drugs

Abstract: In this new era of highly effective oral antiviral drugs for chronic hepatitis C virus (HCV), indications for antiviral treatment may be extendable. This study undertaken to identify suitable candidates for peg-interferon plus ribavirin (PEG-IFN/RBV) treatment by evaluating hepatocellular carcinoma (HCC) risk in patients with chronic HCV treated or not with PEG-IFN/RBV.This large-scale retrospective study was conducted on 1176 patients with chronic HCV without a history of HCC (treatment group [n = 489] and no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…Antiviral treatment and resultant SVR improve the long-term clinical outcome of HCV patients[23-28]. The beneficial effects of IFN-based treatment and SVR on reducing cirrhosis progression, HCC, and mortality have been well documented, and this is reflected by the recently published results from two large-scale studies in Asia and two Chinese cohort studies[29-32]. Similar clinical benefits have been observed with SVR to DAA-based treatment.…”
Section: Clinical Benefits Of Curing Hcv Infectionmentioning
confidence: 95%
“…Antiviral treatment and resultant SVR improve the long-term clinical outcome of HCV patients[23-28]. The beneficial effects of IFN-based treatment and SVR on reducing cirrhosis progression, HCC, and mortality have been well documented, and this is reflected by the recently published results from two large-scale studies in Asia and two Chinese cohort studies[29-32]. Similar clinical benefits have been observed with SVR to DAA-based treatment.…”
Section: Clinical Benefits Of Curing Hcv Infectionmentioning
confidence: 95%
“…HCC develops in hepatitis C patients mostly in the setting of advanced fibrosis and liver cirrhosis [13] . For patients without pre-existing cirrhosis, a higher Fibrosis-4 (FIB-4) index translates to a higher risk of HCC [39] .…”
Section: Advanced Fibrosis and Cirrhosismentioning
confidence: 99%
“…The cumulative risk of HCC development is higher in subjects with high HCV RNA titer than subjects with low titer [45] . SVR results in significantly more favorable long-term outcomes, and decreased risk of progression to cirrhosis and HCC [13,57] . Indeed, a meta-analysis showed that SVR after treatment at any stage of fibrosis is associated with reduced HCC risk [58] .…”
Section: Non-response To the Therapymentioning
confidence: 99%
“…In the article “Assessment of hepatocellular carcinoma risk based on peg-interferon plus ribavirin treatment experience in this new era of highly effective oral antiviral drugs”, [ 1 ] which appeared in Volume 96, Issue 1 of Medicine , an acknowledgment read “This study was supported by an Inha University Hospital grant”. The statement should have read “This study was supported by an Inha University Research grant”.…”
mentioning
confidence: 99%